(untitled) (Revista Espinhaço, 2018)
Population and economic growth have a huge impact on the environment. Since the beginning of the Holocene, about 12,000 years ago, humanity has gone from about 5 million people to billions, and probably reaching over 11 billion by 2100. It was and still has been a spectacular demographic growth. However, the increase of economic activities was several times greater. Global economic growth has accelerated with the beginning of modernity and the European expansion, especially after the Great Navigations and the process of colonization and exploitation of the natural resources of the Americas, though, economic growth became exponential after the Industrial and Energetic Revolution that began in the late eighteenth century. In the period, known as classical modernity, there was great human progress, but, at the same time, environmental regression. This opposition between the material advances of humanity and the material and energetic retreat of ecosystems was maintained and deepened in the late modernity (or postmodernity), allowing even the emergence of a new geological age. In this context, the emergence of the ecocentric environmental sociology came up to analyze the ecological reality of postmodernity. In the field of demography, on the contrary, theoretical and empirical approaches that seek to relate population dynamics with ecological dynamics are still a promise. The objective of this paper is to discuss the relationship between population and development in the Anthropocene and to talk about the challenges posed by the demographic dynamic that takes into account an ecocentric perspective.